Pamphlets and politics in the Dutch Republic - Deen, Femke; Onnekink, David; Reinders, Michel, 1979- (Library of the written word ;, 2011)
The Handpress World explores the impact of the invention of printing by moveable type from the first experiments of the incunabula age through to the end of the eighteenth century. In this crucial period of book history the new technology both transformed established markets for scholarly and religious literature and found a new public through the rise of the pamphlet and later the newspaper. The series will investigate every aspect of this cultural transformation, from the promotion in print of the great intellectual movements of the day through to the birth of the public library. Femke Deen)